Projects with young learners - Phillips, Diane; Dunford, Helen; Burwood, Sarah
This popular series addresses the needs of primary teachers, teacher trainers, and trainee teachers. Each book contains guidance for the teacher, 60 to 100 activities for primary children, and 20 photocopiable worksheets. The activities are explained clearly and simply, with aims, age range and level clearly laid out. Projects with Young Learners Contains practical, tried-and-tested ideas and materials for planning, organizing, and carrying out project work with children aged between 5 and 13. Key Features Combines language and skills development with activities which challenge young learners and motivate them to be independent.
Includes index.
Keywords: Study and teaching (Elementary)